Bibliometric Analysis of Journals, Authors, and Topics Related to Halal Tourism Listed in the Database Scopus by Indonesian Authors - Riduan Mas’ud; Khairul Hamim (Khazanah Pendidikan Islam, 2022)
This study examines the current state of articles on halal tourism written by Indonesian authors and published in journals in the Scopus database. This study outlines traits, popular publications, writers, and subjects related to halal tourism. The Scopus database was used in this study along with bibliometric design analysis to find 65 articles by Indonesian writers that were linked to halal tourism. In August and September of 2021, data collection was done. To explain trends in Indonesian writers from articles, authors, and themes relevant to halal tourism, data were analyzed using Vosviewer and search results in the Scopus database. According to the study's findings, Indonesian authors have published more journal articles about halal travel in the Scopus database over the past few decades. Several publications with Scopus indexes have published articles on Halal tourism written by Indonesian authors. The most viewed journals are Islamic Marketing, and Abror is the author who contributes to the most articles in these publications. Indonesian authors do the most accurate writing on halal tourism, and difficulties with travel locations predominate.